RTP801/REDD1: a stress coping regulator that turns into a troublemaker in neurodegenerative disorders - Canal, Mercè; Romaní-Aumedes, Joan; Martín-Flores, Núria; Pérez-Fernández, Víctor; Malagelada, Cristina (Frontiers in Cellular Neuroscience, 2014)
mTOR (mechanistic target of Rapamycin) pathway regulates essential processes directed to preserve cellular homeostasis, such as cell growth, proliferation, survival, protein synthesis and autophagy. Importantly, mTOR pathway deregulation has been related to many diseases. Indeed, it has become a hallmark in neurodegenerative disorders, since a fine-tuned regulation of mTOR activities is crucial for neuron function and survival. RTP801/REDD1/Dig2 has become one of the most puzzling regulators of mTOR. Although the mechanism is not completely understood, RTP801 inactivates mTOR and Akt via the tuberous sclerosis complex (TSC1/TSC2) in many cellular contexts. Intriguingly, RTP801 protects dividing cells from hypoxia or H2O2-induced apoptosis, while it sensitizes differentiated cells to stress. Based on experimental models of PD, it has been proposed that at early stages of the disease, stress-induced RTP801 upregulation contributes to mTOR repression, in an attempt to maintain cell function and viability. However, if RTP801 elevation is sustained, it leads to neuron cell death by a sequential inhibition of mTOR and Akt. Here, we will review RTP801 deregulation of mTOR in a context of PD and other neurodegenerative disorders.